PP76 Organic food consumption and the incidence of cancer in a large prospective study of women in the UK. (2nd September 2014) - Bradbury, KE; Balkwill, A; Spencer, EA; Roddam, AW; Reeves, GK; Green, J; Key, TJ; Beral, V; Pirie, K
Abstract : Background: Systematic reviews have found few differences in nutrient content between organic and conventional crops, but organic foods are less likely to contain pesticide residues. Pesticide exposure has been linked to a possible increased risk of certain cancer sites, including soft tissue sarcoma, breast cancer, and non-Hodgkin lymphoma. We examined the hypothesis that eating organic food may reduce the risk of cancer in a large prospective study of women. Methods: The study participants included 623, 080 middle-aged UK women with no prior cancer and who had not changed their diet due to illness in the last five years. Women reported their consumption of organic food in 2002, and were followed for cancer incidence over the next 9.3 years. Cox regression models were used to estimate adjusted relative risks by the reported frequency of consumption of organic foods for 17 specific sites or types of cancer and for total cancer. Results: At baseline, 30%, 63% and 7% of women reported never, sometimes or usually/always eating organic food, respectively. Consumption of organic food was not associated with a reduction in the incidence of all cancer (n = 53, 769 cases in total) (RR for usually/always versus never = 1.03, 95% CI: 0.99–1.07), soft tissue sarcoma (RR = 1.37, 95% CI: 0.82–2.27), or breast cancer (RR = 1.09, 95% CI: 1.02–1.15), but was for non-Hodgkin lymphoma (RR = 0.79, 95% CI: 0.65–0.96). Conclusion: In this large prospective study there was little or no decrease in the incidence of cancer associated with consumption of organic food, except possibly for non-Hodgkin lymphoma.